Escrevivências clínicas: violência sexual na vida de meninas negras - um triplo trauma. - Machado, Lilian Paula de Souza Alves (2021)
This work, at first, intended to map the experience of sexual violence in childhood - VSI of black girls and the resonances in their subjectivities. To this end, we outlined the following specific objectives: 1. delineate the place of black women in society and the forms of violence directed to them - specifically sexual violence, historically constituted and legitimated; 2. provide a listening space for the expression of the experience of sexual violence in childhood of black women; and 3. Analyze the procedural modes of subjectivation of Black women in the face of the experience of sexual violence. We adopted the concept of subjectivity as proposed by Guattari and Rolnik, constructed from a field of forces in which the social, the political, and the economic, among other vectors, have an active participation. And, also, intersectionality, a proposition of black feminism that conceives the inextricability between cis-hetero-patriarchy (heteronormatization and naturalization of the father's power), racism, and capitalism. As an approach, we provisionally rely on schizoanalysis, making use of cartography as a methodical path that privileges the hódos - metá (the primacy of walking that traces its goals along the way). Provisional because we also took Frantz Fanon's studies and his contributions to the reflection on racism, racialization, and colonialism. Initially, special attention was given to three clues of the cartographic approach: the establishment of an ethos of trust (shared experience and increased potency to act); the creation of a zone of inter-interest; and the collective of forces as a plan of cartographic experience. In order to listen to the experience reports, four (04) conversation rounds were held in a virtual environment, on consecutive Sunday mornings, when they were asked to tell us about their experiences. The conversations were audio recorded and registered in a logbook and became a space for welcoming, listening, care, legitimization, mutual recognition, and a field for data production. We conceptualized VSI as sexual trauma and, from the analysis plans, in the case of perpetration against black girls, we understood its articulation with the colonial trauma - racism. And, also, a triple articulation - of the two previous ones - with the social trauma. Through the effects of the inside-outside-inside relationship, we observed the resonances inferred by our collaborators and certain subjective settlements that point to the fixity and hardening that the triple traumatic experience produced and continues to produce, not being possible to delineate which effect is produced by which trauma. We also understand that such effects have been internalized, agenciating modes of existence temporarily deprived of power and that have an effect on their ways of being, of desiring, of thinking, and of dreaming. When necessary, our collaborators were referred for free psychotherapeutic counseling.